Stearoyl-CoA Desaturase Activity Is Elevated by the Suppression of Its Degradation by Clofibric Acid in the Liver of Rats - Tomoaki Toyama; Naomi Kudo; Atsushi Mitsumoto; Yasuhide Hibino; Tadashi Tsuda; Yoichi Kawashima (Elsevier, 2007)
A mechanism by which fibrates control stearoyl-CoA desaturase (SCD) in the liver was studied. Treatment of rats with 2-(4-chlorophenoxy)-2-methylpropionic acid (clofibric acid) or feeding of a fat-free diet markedly elevated hepatic activity of SCD. Both the treatment with clofibric acid and the feeding of the fat-free diet caused an increase in the steady-state level of SCD1 mRNA and enhanced transcriptional rate. The half-lives of SCD for control rats, rats treated with clofibric acid rats, and rats fed the fat-free diet were estimated to be 2.0, 3.9, and 1.9 h, respectively. Activity of palmitoyl-CoA chain elongase (PCE) was increased by both clofibric acid treatment and feeding of the fat-free diet as was observed with SCD. Steady-state level of rat fatty acid elongase 2 mRNA was increased by the treatment with clofibric acid or feeding of fat-free diet, although the transcriptional rate was not altered. Different from SCD, PCE was highly stable and its half-life was not changed by either clofibric acid or fat-free diet. These results strongly suggest that the decreased degradation of SCD is responsible for the increase in its activity in addition to increased transcription of SCD1 in the rats treated with clofibric acid. Keywords:: stearoyl-CoA desaturase, protein degradation, palmitoyl-CoA chain elongase, clofibric acid